A clinical observational study on the application of enhanced recovery after laparoscopic pancreaticoduodenectomy - Liao, Rui; Li, Jun-Cai; Chen, Jie; Wei, Xu-Fu; Yan, Xiong (Frontiers in Surgery, 2022)
Purpose The safety and feasibility of enhanced recovery after surgery (ERAS) for laparoscopic pancreaticoduodenectomy (LPD) are unclear. The aim of this retrospective clinical study was to evaluate the impact of ERAS protocols for LPD. Patients and methods Between March 2016 and December 2018, a total of 34 consecutive patients with ERAS for LPD were prospectively enrolled and compared with 68 consecutive patients previously treated for non-ERAS after LPD during an equal time frame. The intraoperative and postoperative data were collected and comparatively analyzed. Results The mean length of postoperative hospital stay (15.8 ± 3.4 and 23.1 ± 5.1 days, P < 0.001) was reduced significantly in ER group than those in non-ER group. The operation time (462.7 ± 117.0 vs. 450.9 ± 109.8 min, P = 0.627) and intraoperative blood loss (523.5 ± 270.0 vs. 537.5 ± 241.8 ml, P = 0.800) were similar in the two groups. The complications (ER: 32.4% vs. non-ER: 35.3%, P > 0.05) and their severities (Clavien–Dindo grade ≥3 complications, 2 vs. 5 patients; P = 0.783) of patients with ERAS protocols were not increased. No difference in mortality and readmission rates was found. Finally, the total medical costs (2.1 ± 0.7 × 104 and 2.3 ± 0.7 × 104, P = 0.017) in ER group were lower than those in non-ER group. Conclusion the ERAS is safe and effective in the perioperative period of LPD. It could effectively reduce the length of postoperative stay and medical costs, and does not increase the incidence of postoperative complications.